Nano-sized Metal and Metal Oxide Modified Electrodes for Pharmaceuticals Analysis - Topal, Burcu D.; Sener, Ceren Elif; Kaya, Basak; Ozkan, Sibel Aysıl (Current Pharmaceutical Analysis, 2021)
The electrochemical analysis offers a number of important advantages such as providing information on pharmaceuticals analysis and their in vivo redox processes and pharmacological activity. The interest in developing electrochemical sensing devices for use in clinical assays is growing rapidly. Metallic nanoparticles can be synthesized and modified with various chemical functional groups, which allow them to be conjugated with antibodies, ligands, and drugs of interest. In this article, the novel developments to enhance the performance of sensor modified with metal nanoparticles of pharmaceuticals were reviewed. A discussion of the properties of metal nanostructures and their application in drug analysis is presented. Their application as a modifier agent in determining low levels of drugs in pharmaceutical dosage forms and biological samples is discussed. It has been found that the electrocatalytic effect of the electrode, sensitivity and selectivity were increased using various working electrodes modified with nano-sized metal, metal oxide and metal/metal oxide particles.
Keywords: Drug analysis